Bordetella Type III Secretion Injectosome and Effector Proteins - Kamanova, Jana (Frontiers in cellular and infection microbiology, 2020)
Pertussis, also known as whooping cough, is a resurging acute respiratory disease of humans primarily caused by the Gram-negative coccobacilli Bordetella pertussis, and less commonly by the human-adapted lineage of B. parapertussisHU. The ovine-adapted lineage of B. parapertussisOV infects only sheep, while B. bronchiseptica causes chronic and often asymptomatic respiratory infections in a broad range of mammals but rarely in humans. A largely overlapping set of virulence factors inflicts the pathogenicity of these bordetellae. Their genomes also harbor a pathogenicity island, named bsc locus, that encodes components of the type III secretion injectosome, and adjacent btr locus with the type III regulatory proteins. The Bsc injectosome of bordetellae translocates the cytotoxic BteA effector protein, also referred to as BopC, into the cells of the mammalian hosts. While the role of type III secretion activity in the persistent colonization of the lower respiratory tract by B. bronchiseptica is well recognized, the functionality of the type III secretion injectosome in B. pertussis was overlooked for many years due to the adaptation of laboratory-passaged B. pertussis strains. This review highlights the current knowledge of the type III secretion system in the so-called classical Bordetella species, comprising B. pertussis, B. parapertussis, and B. bronchiseptica, and discusses its functional divergence. Comparison with other well-studied bacterial injectosomes, regulation of the type III secretion on the transcriptional and post-transcriptional level, and activities of BteA effector protein and BopN protein, homologous to the type III secretion gatekeepers, are addressed.
Keywords: effector protein; Sheep; Bordetella; sekreční systém typu III; Bordetella bronchiseptica; BteA/BopC; BopN; zvířata; Bordetella pertussis; type III secretion system; bakteriální proteiny; faktory virulence; Bordetella Infections; Type III Secretion Systems; pertussis; Bacterial Proteins; Animals; infekce bakteriemi rodu Bordetella; Virulence Factors; ovce